Resource constraints in implementing electronic document management systems - A.E. Plakhin; E.S. Ogorodnikova; K.V. Rostovtsev (Цифровые модели и решения)
The relevance of the study of the level of implementation of electronic document management systems by Russian companies and the definition of resource constraints for the implementation of these systems is due to modern conditions characterized by significant restrictions on the activities of Russian business, including in the field of business process informatization. The research method uses the analysis of state statistics data on the provision of Russian enterprises with software and personnel in the IT field. The results of the study showed that the key resource limitations of the introduction of electronic document management systems are the need to compensate the costs of issuing EDS for all types of organizations, high costs of purchasing ready-made solutions for small and medium-sized businesses, the need to provide Internet access and purchase special equipment and expand the staff of IT specialists.